Cover Feature: Structural Effects of Fusicoccin upon Upregulation of 14‐3‐3‐Phospholigand Interaction and Cytotoxic Activity (Chem. Eur. J. 60/2018). Issue 60 (22nd October 2018) - Ohkanda, Junko; Kusumoto, Atsushi; Punzalan, Louvy; Masuda, Ryoma; Wang, Chenyu; Parvatkar, Prakash; Akase, Dai; Aida, Misako; Uesugi, Motonari; Higuchi, Yusuke; Kato, Nobuo
Abstract : Fusicoccin, a phytotoxic diterpene glucoside, was converted to a series of antiproliferative agents for tumor cells by removing 12‐hydroxyl group semi‐synthetically. These compounds were shown to upregulate interaction of 14‐3‐3 and a phospholigand in a sequence‐specific manner. More information can be found in the Full Paper by J. Ohkanda et al. onpage 16066 .